MENGENAL KUTUB TIS’AH DAN BIOGRAFI PENGARANGYA (Imam Malik, Imam Ahmad Ibn Hambal Dan Al-Damiri) - Muhammad Qomarullah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2017)
The Qur'an is the basic source of Islamic Shariah are no doubts, because the Qur'an is the word of Allah as revealed to the prophet Muhammad, and became the main source of law in Islam while the sources of law is al-Sunnah. We can know that Ahmad Ibn Hanbal, Imam Malik and Al Damiri is a relatively most legal scholars textual understanding of the Qur'an and the Sunnah. His love for the sunnah and hadith of the Prophet, so do not be surprised if today the results of their work are retained and used as a reference for scientists in studying the science of hadith.